Cognitive Function in Duchenne Muscular Dystrophy Patients - Urbanovič, Viktorija; Grikinienė, Jurgita (Neurologijos seminarai, 2024)
Duchenne muscular dystrophy is a rare, progressive, X-linked recessive disorder, characterized by impaired synthesis of the protein dystrophin. Motor symptoms in boys typically emerge within the first year of life, followed by progressive cardiac involvement. In recent years, an increasing body of research has highlighted the role of dystrophin in brain development and function, with notable impacts on cognitive performance and language development. It has been observed that boys with Duchenne muscular dystrophy are frequently diagnosed with intellectual impairment, verbal memory impairment, learning and reading difficulties. Among the earliest developmental concerns, often, a language delay is manifested. Increasing evidence supports a link between the absence of specific dystrophin isoforms and intellectual disabilities. Mutations in the distal regions of the dystrophin gene, affecting isoforms such as Dp140 or Dp71, are associated with a higher risk of cognitive impairment and more severe intellectual disability. This paper provides a literature review on cognitive function in Duchenne muscular dystrophy.
Keywords: Duchenne muscular dystrophy; cognitive function; intellectual impairment